1972
DOI: 10.1111/j.1432-1033.1972.tb02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism of Avian‐Erythrocyte Chromatin and Ethidium Bromide Bound to Chromatin

Abstract: The circular dichroism of mature gander erythrocyte chromatin was compared with that of partially dehistonized chromatin and deproteinized DNA. The ellipticity at 275 nm for native chromatin was found to be three-times less than that for DNA. The 275-nm transition was gradually increased in magnitude upon removal of histones. Selective removal of the very lysinerich histone I and the erythrocyte-specific histone V, but not histone I alone, resulted in a significant increase in transcription in vitro and ethidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In the region of the spectrum above 240 nm there is a progressive transition with increasing HCHO concentration from a native chromatin spectrum (Simpson and Sober, 1970;Shih and Fasman, 1970;Boffa et al, 1971;Fric and Sponar, 1971;Hanlon et al, 1972;Johnson et al, 1972;Williams et al, 1972), to one which closely resembles the spectra of films of the Li salt of naked DNA2 (TunisSchneider and Maestre, 1970). For purposes of discussion in this paper we shall refer to this as the "suppressed" spect r~m .~ Below 240 nm, where the major contributor to CD is protein , there is little change in the chromatin spectrum upon fixation with HCHO.…”
Section: Resultsmentioning
confidence: 91%
“…In the region of the spectrum above 240 nm there is a progressive transition with increasing HCHO concentration from a native chromatin spectrum (Simpson and Sober, 1970;Shih and Fasman, 1970;Boffa et al, 1971;Fric and Sponar, 1971;Hanlon et al, 1972;Johnson et al, 1972;Williams et al, 1972), to one which closely resembles the spectra of films of the Li salt of naked DNA2 (TunisSchneider and Maestre, 1970). For purposes of discussion in this paper we shall refer to this as the "suppressed" spect r~m .~ Below 240 nm, where the major contributor to CD is protein , there is little change in the chromatin spectrum upon fixation with HCHO.…”
Section: Resultsmentioning
confidence: 91%
“…At lysine/DNA-phosphate ratios of approximately 0.5 it was noted that in each case the D N A portion of the spectrum was reminiscent of spectra seen in chromatin isolated from various sources (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). That is, the single band a t 275 nm in the spectrum of the native DNA shifted over to a smaller positive band a t approximately 282 nm upon complex formation with polymers I11 and IV (Figs.…”
Section: Resultsmentioning
confidence: 94%
“…Angerer et al (1974) showed that there are at least two classes of highly fluorescent strong binding sites in deoxyribonucleoprotein (DNP) as compared to only one class in DNA. The restriction of the ethidium bromide-binding capacity of D N P appears to be due to t h e f l lysine-rich histone for calf thymus D N P (Angerer et al, 1974) and to the lysine-rich histone P and the histone V for chickblood D N P (Williams et a!., 1972).…”
Section: Interaction With Dnamentioning
confidence: 91%